Effect of Cut-Off Angles on Observational Accuracy in GPS Measurements - محمد, هشام; فايز ديب; ندى محفوض (Latakia University Journal -Engineering Sciences Series, 2024)
This scientific study investigates the impact of cut-off angles on the accuracy of measurements obtained using the Global Positioning System (GPS) and evaluates the effect of varying cut-off angles on precision. Data from measurements conducted at five different cut-off angles (0º, 5º, 10º, 15º, 20º) were analyzed. After reviewing the standard deviations (Std Dev) for the North (N), East (E), Up (U), and Horizontal (Hz) components, variable responses to changes in cut-off angles were detected. This study provides a comprehensive analysis of the effects of cut-off angles on GPS measurements. Cut-off angles determine the minimum elevation angle above the horizon at which GPS satellites are considered visible and trackable by the receiver. Understanding the consequences of choosing specific cut-off angles is crucial for enhancing GPS-based applications and research. In this study, we will focus on testing the effect of cut-off angles on the following aspects: Satellite Visibility. Positioning Accuracy. Signal Strength and Multipath Effects.